2017
DOI: 10.1103/physrevfluids.2.103502
|View full text |Cite
|
Sign up to set email alerts
|

Scaling relations in large-Prandtl-number natural thermal convection

Abstract: In this study, we follow Grossmann and Lohse [Phys. Rev. Lett. 86, 3316 (2001)], who derived various scalings regimes for the dependence of the Nusselt number Nu and the Reynolds number Re on the Rayleigh number Ra and the Prandtl number Pr. We focus on theoretical arguments as well as on numerical simulations for the case of large-Pr natural thermal convection. Based on an analysis of self-similarity of the boundary layer equations, we derive that in this case the limiting large-Pr boundary-layer dominated re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
4
37
1
Order By: Relevance
“…For the convection roll states we find that the effective scaling exponent γ Nu in Nu ∼ Ra γ Nu is approximately 0.3. It increases with increasing Γ r , reaching approximately 1/3 for the largest Γ r = 8, which is the value predicated by the Grossmann-Lohse (GL) theory for the I < ∞ and III ∞ regimes (Grossmann & Lohse 2000Shishkina et al 2017) for the no-slip case. For zonal flow γ Nu is much smaller, namely only 0.17.…”
Section: Nusselt Number and Reynolds Numbermentioning
confidence: 65%
“…For the convection roll states we find that the effective scaling exponent γ Nu in Nu ∼ Ra γ Nu is approximately 0.3. It increases with increasing Γ r , reaching approximately 1/3 for the largest Γ r = 8, which is the value predicated by the Grossmann-Lohse (GL) theory for the I < ∞ and III ∞ regimes (Grossmann & Lohse 2000Shishkina et al 2017) for the no-slip case. For zonal flow γ Nu is much smaller, namely only 0.17.…”
Section: Nusselt Number and Reynolds Numbermentioning
confidence: 65%
“…So far, the LSC and BL properties have mainly been studied in cells featuring a small aspect ratio Γ , typically Γ = 1/2 or Γ = 1. Various studies have shown that the BLs indeed follow the laminar Prandtl-Blasius (PB) type predictions in the classical regime (Ahlers et al 2009;Shi, Emran & Schumacher 2012;Stevens et al 2012;Shishkina et al 2015;Schumacher et al 2016;Shishkina et al 2017a). Previous studies by, for example, Wagner, Shishkina & Wagner (2012) and , have used results from direct numerical simulations (DNS) in aspect ratio Γ = 1 cells to study the properties of the BLs in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Direct numerical simulations (DNS) exhibit much more flexibility from the standpoint of diffusivity coefficients and have proved invaluable for understanding the role on the Prandtl number for both RBC (Shishkina etal. 2017) and HC (Shishkina & Wagner 2016). In the present study, we employ DNS to explore the parameter space of CISS.…”
Section: Introductionmentioning
confidence: 99%